EARLY CHILDHOOD TEACHERS’ TEACHING PHONICS STRATEGIES AND THEIR REPORTED BELIEFS TO ASSIST PRIOR-TO SCHOOL CHILDREN IN ACQUIRING ENGLISH ALPHABET KNOWLEDGE AS A FOREIGN LANGUAGE (A CASE STUDY OF THE EARLY YEARS TEACHERS OF BEE BE GYM BABIES AND TODDLERS - Farida, Nuzulia Nur; Kalisa, Pasca (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study aimed at (1) discovering the early years teachers’ self-reported teaching phonics strategies in practices to teach alphabet knowledge and skills to their prior to school students, and (2) analyzing the teachers’ self-reported beliefs in their teaching phonics strategies used to teach alphabet knowledge and skills to their prior to school students. This study used a descriptive qualitative method. The participants of the study were ten non-native talented teachers experienced in teaching phonics to the young learners students. The instruments of collecting data were questionnaire and interview. The data were obtained by using a direct survey and a semi-structured interview. The direct survey was used to investigate the early childhood teachers’ teaching phonics strategies in practices, while to enhance the potential to understand self-reported teachers’ beliefs in appropriate early literacy teaching strategies, the researcher did the interview. Based on the findings, dealing with the phonics teaching strategies, the teachers were mostly using either commercial phonics program and play based literacy learning strategies to teach alphabet knowledge and skills to their students within the commercial phonics program over largely focused on their service rather than the play-based literacy learning strategies. In addition, from the interview, it could be concluded that the teachers believed that play could not be separated in the children’s learning process. Both systematic and incidental learning process as well as componential and child-centered views were crucial in the children’s acquiring literacy process and should be integrated.